Living with or beyond lymphoma: A mixed methods investigation of the unmet needs of cancer survivors. - Boland, Vanessa (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
Background: The burden of cancer is set to increase thanks to success in treatment modalities and increasingly ageing populations. This is especially true for lymphoma survivors, the largest cohort of haematological malignancies. Mortality and survival rates for lymphoma continue to improve, with rising numbers of survivors living with or after a diagnosis of lymphoma after five years. However, lymphoma remains understudied in survivorship literature. Identifying problems during survivorship is a pressing concern for service planning and healthcare delivery. The anticipated surge in the annual numbers of new lymphoma cases over the coming decades is a clear signal for sound investment in survivorship planning and care delivery. Identifying the unmet needs of this cohort is required to ensure that future developments are tailored to meet their specific needs. Aim: This study was designed to comprehensively investigate the unmet needs of adult lymphoma survivors. This research aims to examine the unmet needs of lymphoma survivors to guide policy, practice, and future research to be responsive in addressing these needs. This thesis strives to overcome previous research limitations and evaluate the unmet needs of lymphoma survivors using a quantitative survey and qualitative interviews to give a voice to the lymphoma survivor. Methodology and Methods: A pragmatic mixed methods sequential explanatory design was considered the most suitable approach to address the research objectives and facilitate a comprehensive understanding of the magnitude and context of the unmet needs experienced by lymphoma survivors. In phase one, a purposive sample of adult lymphoma survivors (N=205) was recruited from five hospitals and via supplementary online recruitment through cancer support centres in Ireland. Lymphoma survivors one to five years post-diagnosis completed a survey including the Short-Form Survivor Unmet Needs Survey, Functional Assessment of Cancer Therapy-Lymphoma Survey and EuroQol Five-Dimension Five-Level Survey. The survey asked participants about their unmet needs and quality of life outcomes as a result of lymphoma. In phase two, a subsample of 14 survey participants participated in semi-structured interviews to add context to the unmet needs and experiences of lymphoma survivors in Ireland. Findings: Integrated findings revealed a significant and directional link between unmet needs and quality of life outcomes among lymphoma survivors. Canonical correlational analysis confirmed that an increase in lymphoma survivors' quality of life is associated with a statistically significant decrease in unmet needs (p=<.001). Descriptive statistics showed the most prevalent concerns for higher unmet needs and lower quality of life were feeling tired (73-83%) and coping with a bad memory or focus (67-69%). Lymphoma survivors' narratives provided an enhanced understanding of the consequences on daily living, like the inconvenience of forgetfulness, a lack of focus, or sleep as a treatment for tiredness. Both datasets also reported nausea and vomiting, weight changes and night sweats, but interview data provided further insights not captured by the phase one survey, such as reproductive health concerns and chemotherapy-induced alopecia. Inferential statistics found that being female, younger, not having private health insurance or having a more recent lymphoma diagnosis (one to three years post-diagnosis versus three to five years post-diagnosis) were consistent factors that contributed to higher unmet needs (all p=<.05). Interview data explained the experience of younger survivors who highlighted challenges associated with their life stage, including delayed diagnosis and perceived setbacks in achievements or milestones. This study underscores the importance of timely cancer care, as evidenced by both survey responses and qualitative accounts. Unaddressed unmet physical needs contributed to unmet emotional and psychological needs due to the uncertainty experienced by survivors in seeking support to address their health concerns. This emphasises the importance of time in the journey to diagnosis and getting appointments or test results. After addressing physical health concerns, psychological and emotional needs were the dominant problems which survivors prioritised. Qualitative data revealed the importance of social support in coping with lymphoma-related challenges, although survivors often hesitated to burden their families. This study also highlights concerns about compromised immunity, infection risk, and feelings of isolation, particularly exacerbated by the pandemic. Financial problems, work-related challenges, and difficulties navigating the healthcare system further contributed to survivors' distress. While statistical analysis suggests a link between lower emotional and physical well-being and higher unmet informational needs (p=<.05), qualitative accounts shed light on insufficient awareness and understanding of lymphoma, leading to gaps in information provision and fragmented care. Discussion and Conclusion: Lymphoma survivors have a myriad of interconnecting unmet needs which have reciprocal relationships with quality of life outcomes; better quality of life corresponds with fewer unmet needs. This study found consistent factors associated with higher unmet needs, yet a lymphoma diagnosis's heterogeneous and individualised nature requires thoughtful consideration. The problematic and often prolonged time to diagnosis spotlighted this inherent heterogeneity in the presentation of lymphoma, which can inadvertently be interpreted as not serious or cancer-related, and that this is a cancer that crosses the lifespan, which has inherent challenges relating to the nuances of life stage. These findings emphasise the importance of tailored support for lymphoma survivors. Yet, barriers to effective survivorship cancer care in identifying how it should be set up, who should monitor, assess, and develop the service and what specific patient groups will benefit from it. This research has identified that lymphoma would benefit from survivorship support in the period one to five years post-diagnosis, as participants reported dealing with a myriad of unmet needs across various domains. A tailored approach to follow-up care will likely be required, supported by an integrated care model for cancer care services. Effectively, cancer centres require access to a range of expertise, resources and joined-up thinking to meet the needs of the survivor population. The appropriate investment and infrastructure are fundamental to their efficiency and effectiveness. Multiple aspects of lymphoma survivorship would benefit from an enhanced understanding and awareness of lymphoma as a type of cancer. Clinically, survivorship services would benefit from the routine assessment of survivors' unmet needs; this study has provided evidence for selecting valid and reliable instruments for use in this cohort. Future research should endeavour to address the sparse focus on lymphoma-specific research and disparate reporting, which to date has impaired the emphasis of this group at policy level with direct implications to practice and allocation of resources.
APPROVED
Keywords: Cancer survivorship; Blood cancer; Mixed methods; Mixed method sequential explanatory; Unmet needs; Quality of life; Lymphoma; Cancer; Haematological malignancy